Desafios e potencialidades da atuação do conselho de alimentação escolar durante a pandemia de covid-19 - BENICIO, Suele dos Santos (2024)
The PNAE is recognized as the oldest public policy in the area of food and nutrition security in Brazil, considered one of the largest programs in the world when it comes to universal service to students and guaranteeing the human right to adequate and healthy food. As a result, its execution needs to be monitored, with the School Food Councils (CAE) coming into action, which is a body whose attribution is to guarantee the effectiveness of this execution and, thus, contribute to the achievement of the program's objectives, especially in terms of to the integral development of students. However, it was during the Covid-19 pandemic that its action became even more necessary, not only due to the period, but also due to the food insecurity that the country was facing and the dismantling of public policies that was taking place, since the PNAE was one of these policies and given the social and economic relevance of the program. The objective was to analyze how the CAE contributed to the PNAE ensuring the right to adequate food and nutrition and the food and nutritional security of students, during the Covid 19 pandemic, in the year 2021, in Pará municipalities. This is a cross-sectional, descriptive-retrospective study based on document analysis of articles on PNAE, CAE and the pandemic, PNAE legislation and audiovisual resources. The speeches of counselors from 8 (eight) recordings of a total of 4 (four) virtual meetings, which took place in the year 2021, on two consecutive days, lasting 4 hours, were analyzed. For the transcription of the counselors' speeches, listening was performed first and then writing in Microsoft Word, the free online tool Web Captioner was also used, which performs transcriptions through voice recognition. Soon after, the analysis of the data obtained was carried out observing the objectives of this work. The transcription of the speeches generated 4 documents in Word with 32, 29, 25, 30 pages each, and a quantity of 119 speeches. The results found were exposed in two topics, being Challenges pointed out in the speeches and then Potentialities pointed out in the speeches. Within the Challenges topic, the subtopics were generated: Lack of support from Eex / lack of disclosure by the CAE; Logistic/financial/planning/universal service to all students enrolled in schools during the pandemic period and intervention by other control bodies; Lack of qualification and adequate training/knowledge; Difficulties in the composition/renewal of the CAE/lack of interest in participating; Infrastructure/lack of adequate location, computer equipment and human resources for the execution and recording of activities carried out by the CAE. As for the potentialities, the following were generated: Collective thinking and support from EEX; Sharing experiences, knowledge / partnership with other bodies; Articulation between the actors involved in the execution of the PNAE; Importance of training promoted by CECANE. Given the context found, the study shows that the CAE faces the most diverse challenges facing the implementation of the PNAE, which are recurrent, but subject to solution. For this, it will be necessary that all those involved in the execution of the program assume their role responsibly. The findings demonstrate that the executing entities are exempting themselves from their role within the program, and that, even without much guidance and support, the CAE has been able to contribute to the SAN and DHANA of the students.